A method for preparing complex-shaped parts of tungsten-copper alloy for high-airtightness packaging
Through the preparation and injection molding process of ultra-fine tungsten-copper composite powder, combined with degreasing, sintering and hot isostatic pressing, the problems of low material utilization and high leakage rate of tungsten-copper complex-shaped parts are solved, achieving high air tightness and Preparation of tungsten-copper alloy parts with low leakage rate.
Patent Information
- Application Number
- CN202310593334.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-05-24
AI Technical Summary
The prior art is difficult to effectively solve the problems of low material utilization, high machining costs and low efficiency of complex-shaped parts in tungsten copper heat sink materials, and it is difficult to meet the requirements of high-air-tight packaging devices.
Ultra-fine tungsten-copper composite powder is prepared through wet mixing and mechanical alloying methods, combined with injection molding, degreasing, sintering and hot isostatic pressing processes to prepare tungsten-copper alloy complex-shaped parts for high airtight packaging.
The density of tungsten copper alloy parts has been increased to more than 99%, and the leakage rate is ≤1×10-9Pa·m3/s, which meets the requirements of high airtightness and low leakage rate packaging devices, while reducing the preparation cost.
Smart Images

Figure CN117840434B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of complex parts for metal packaging, and in particular to a method for preparing a complex-shaped tungsten-copper alloy part for high-airtightness packaging. Background Art
[0002] Metal packaging is a form of electronic packaging that uses metal as a shell or base, the chip is installed on the shell or base directly or through a substrate, and the leads pass through the metal shell or base. Most of them use glass-metal sealing technology. Metal packaging has the advantages of high precision, excellent heat dissipation and electromagnetic field shielding performance, good sealing, high reliability, easy processing, and suitability for mass production. It is widely used in optoelectronics, microwaves, radio frequency, surface acoustic waves, and high-power devices. As one of the key components of metal packaging, the shell (also known as the shell or tube shell) and the base mainly play the role of circuit support, optoelectronic signal transmission, heat dissipation, electromagnetic shielding, sealing and chemical protection, which directly affects the reliability of the device.
[0003] As metal packaging develops towards high-density integration, the power efficiency of active chips can only reach 15-40%. A large amount of input power will be dissipated in the form of redundant heat, and the reliability of electronic components decreases by about 10% for every 2°C increase in temperature. Therefore, under the condition that the volume and weight of the heat dissipation structure are constrained, efficient heat dissipation has become one of the focus issues in the packaging field. The shell or base provides mechanical and environmental protection for the internal chips and circuits. On the one hand, the thermal expansion coefficients of these components are required to match to ensure the reliability of the shell sealing performance within the entire operating temperature range; on the other hand, they are required to dissipate the heat generated by the chip when it is working in a timely manner. Tungsten-copper alloy (W-Cu) and Kovar alloy (Kovar) are the most common shell and base packaging materials in metal packaging. Tungsten-copper alloy is a metal-based composite material. The tungsten and copper phases are neither miscible nor form compounds. The tungsten skeleton can control the thermal expansion coefficient of the material, making it close to the expansion coefficient of semiconductor chip materials such as single crystal silicon, silicon carbide, gallium nitride, and gallium arsenide, while the continuous copper phase can keep the material at a high thermal conductivity, thereby improving the reliability of the device. Therefore, for active devices that generate a large amount of heat or require a stable operating temperature, the shell can be made of tungsten-copper alloy as a whole, or a structure combining a tungsten-copper base and a Kovar frame can be used to achieve good heat dissipation function.
[0004] In common tungsten copper heat sink materials for metal packaging, the copper content is generally in the range of 10-30wt.%. The ratio of tungsten to copper can be adjusted as needed to change the thermal expansion coefficient of the material to match the chip. At present, the production method of tungsten copper heat sink materials is mainly achieved by sintering a tungsten skeleton and then melting and infiltrating copper. This process mainly has the following two problems: (1) The selection of tungsten powder raw materials, the pressing and sintering of the tungsten skeleton, and the melting and infiltrating copper process have high requirements. The existence of closed holes in the tungsten skeleton or improper copper infiltration process will leave residual micropores in the material, thereby affecting the thermal conductivity of the material, subsequent surface treatment and welding, etc., resulting in poor consistency of the final product; (2) The melting and infiltration process can generally only produce semi-finished products with simple shapes, and subsequent machining is required to obtain the final product. For products with complex shapes such as shells and bases, the material utilization rate may sometimes be as low as 20%. At the same time, the machining cost is high and the production efficiency is low. Therefore, the traditional method of sintering a tungsten skeleton and then melting and infiltrating copper is not suitable for products with complex shapes. The technical solution disclosed in the patent application document with publication number CN101450381A effectively improves the consistency of the product by adding electrolytic copper powder as an inducer to the raw tungsten powder and using copper liquid infiltration instead of traditional melt infiltration. However, it still cannot solve the problems of low material utilization, high machining cost, and low efficiency of complex-shaped heat sink products. With the rapid development of 5G, big data, blockchain, cloud computing, the Internet of Things, artificial intelligence, national defense and military industries, the demand for complex-shaped products such as tungsten copper shells and bases for metal packaging in optical communications and microwave communications is increasing. The traditional copper infiltration and machining processes are long, costly, and inefficient, and can no longer meet the market's demand for the cost and production capacity of such complex-shaped tungsten copper parts. This field urgently needs new processes to solve the current dilemma.
[0005] The use of near-net forming (also known as near-net forming) technology represented by Metal Injection Molding (MIM) to achieve efficient production of tungsten copper shells and bases has attracted more and more attention from the industry and is also considered an important direction to solve the current technical barriers. However, since tungsten copper is a pseudo-alloy that is immiscible in two phases, obtaining products with uniform microstructure and high density has become a technical difficulty in tungsten copper injection molding. The current research progress is as follows:
[0006] The technical solution disclosed in the patent application document with publication number CN110172598A is to obtain a pure tungsten skeleton by injection molding, degreasing and sintering tungsten powder, and then perform traditional copper infiltration. Although this process can prepare parts with complex shapes, it is difficult to infiltrate special-shaped parts with copper, and it is difficult to obtain products with uniform organization, high density and good consistency; on the other hand, it is difficult to remove the excess copper on the surface of the parts after copper infiltration, and it is impossible to achieve near-net forming. The technical solution disclosed in the patent application documents with publication numbers CN114535589A and CN104928851A is to increase the solid solubility of W in Cu, promote liquid phase sintering, and improve the sintering density of tungsten-copper alloy by adding one or more activation element powders such as Co, Fe, Ni, and Pd to the raw material powder of injection molding. However, adding such transition metal elements to achieve activated sintering, as mentioned in the patent application document with publication number CN115464144A, will significantly affect the thermal conductivity of the material even if the addition amount is very low. In order to improve the sintering density and thermal conductivity of injection molded tungsten copper parts, the technical solutions disclosed in the patent application documents with publication numbers CN1247372C and CN115464144A use tungsten and copper precursors to mix in a certain proportion, then reduce to obtain tungsten copper composite powder, and then obtain heat sink parts with complex shapes through injection molding. The density of the material can only reach 96% at most. The technical solution disclosed in the patent application document with publication number CN114086015A uses spherical tungsten powder with an average particle size of 2-3μm and copper powder with an average particle size of 6-8μm to mechanically mix, and then mix and granulate with a paraffin-based binder. After injection molding, degreasing and sintering, hot isostatic pressing is used to further improve the density of the material. The temperature of hot isostatic pressing is 800-1000℃ and the pressure is 100-150MPa. The density of the material after hot isostatic pressing can reach more than 98%. However, the technology mainly has the following problems and disadvantages:
[0007] (1) Spherical tungsten powder is generally prepared by plasma spheroidization or explosive wire method, which is very expensive.
[0008] (2) When micron-sized tungsten powder and copper powder are mixed mechanically, the mixing may be uneven due to the large difference in density. At the same time, during the injection filling process, the high shear rate is prone to segregation, resulting in uneven microstructure of the final product.
[0009] (3) Due to the use of micron-sized tungsten powder, the relative gap between tungsten particles is large during the liquid phase sintering process. If the sintering temperature is too low, the density of the sintered part is not enough, and there are interconnected holes inside the material, which will lead to poor subsequent hot isostatic pressing effects, and finally there will be more residual micropores inside the product; if the sintering temperature is too high, there will not be enough capillary force between the tungsten particles, causing the copper liquid to be squeezed out of the part, thereby affecting the copper content and uniformity of the tungsten-copper alloy, and even leaving holes where the copper liquid flows away. These defects are difficult to eliminate in the subsequent hot isostatic pressing. The above two situations will lead to a decrease in the airtightness of the tungsten-copper material, making it difficult to meet the requirements of high-airtightness packaging devices. Summary of the invention
[0010] In view of the above problems in the prior art, the present invention provides a method for preparing complex-shaped tungsten-copper alloy parts for packaging with high airtightness and low leakage rate, which further improves the density of the product at a lower preparation cost.
[0011] The technical solution adopted by the present invention is as follows:
[0012] A method for preparing a complex-shaped tungsten-copper alloy part for high-airtightness packaging comprises the following steps:
[0013] (1) preparing ultrafine tungsten-copper composite powder by any of the following methods: wet mixing of tungsten precursor and copper precursor, followed by drying, calcining and reducing; or mixing of tungsten oxide and copper oxide, followed by calcining and reducing; or mixing of tungsten powder and copper powder, followed by mechanical alloying;
[0014] The average particle size of the obtained ultrafine tungsten-copper composite powder is no more than 1 μm, the mass fraction of copper in the tungsten-copper composite powder is 5-40%, and the tungsten-copper powder is evenly mixed;
[0015] (2) Ultrafine tungsten-copper composite powder and organic binder are mixed and granulated to prepare a feed for injection, which is then injected into a mold. After demolding, an injection blank of the part is obtained, and then degreasing, high-temperature sintering and hot isostatic pressing are performed to obtain a tungsten-copper alloy complex-shaped part for high-airtightness packaging, wherein the high-temperature sintering temperature is 1100-1600°C, and the sintering atmosphere is one of pure hydrogen, hydrogen-nitrogen mixed gas or ammonia decomposition gas; the hot isostatic pressing temperature is 1084-1150°C, the pressure is 100-200MPa, and the atmosphere is argon.
[0016] Furthermore, the average particle size of the ultrafine tungsten-copper composite powder is 0.4-0.9 μm.
[0017] Furthermore, the organic binder is a paraffin-based binder or a polyoxymethylene-based binder, and the weight proportion of the organic binder to the total material is 3-10%.
[0018] Furthermore, the paraffin-based adhesive is composed of the following components in weight percentage: 52% paraffin, 28% polyethylene, 10% polypropylene, 8% polyethylene glycol, and 2% stearic acid.
[0019] More preferably, the degreasing operation corresponding to the paraffin-based binder includes solvent degreasing and thermal degreasing performed in sequence.
[0020] Furthermore, the polyoxymethylene-based adhesive is composed of the following components in weight percentage: 89% polyoxymethylene, 6% high-density polyethylene, 3% polypropylene, and 2% ethylene-vinyl acetate copolymer.
[0021] More preferably, the degreasing operation corresponding to the polyoxymethylene-based binder includes catalytic degreasing and thermal degreasing performed sequentially.
[0022] In summary, compared with the prior art, the present invention has the following advantages and beneficial effects:
[0023] 1. The present invention only requires that the tungsten powder and copper powder reach the level of ultrafine powder, and is not limited to a specific morphology. There are many preparation options, and the preparation cost is low;
[0024] 2. The present invention can increase the density of the target product to more than 99%, and the leakage rate is ≤1×10 -9 Pa·m 3 / s, meeting the requirements of high airtightness and low leakage rate packaging devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a microscopic electron microscope scanning image of the ultrafine tungsten-copper composite powder prepared in Example 1;
[0026] Figure 2 This is a schematic diagram of the structure of the tungsten-copper alloy shell prepared in Example 1;
[0027] Figure 3 This is a microscopic electron microscope scanning image of the ultrafine tungsten-copper composite powder prepared in Example 2;
[0028] Figure 4 This is a schematic diagram of the structure of the tungsten-copper alloy shell prepared in Example 2;
[0029] Figure 5 This is a microscopic electron microscope scanning image of the ultrafine tungsten-copper composite powder prepared in Example 3;
[0030] Figure 6 This is a schematic diagram of the structure of the tungsten-copper alloy shell prepared in Example 3;
[0031] Figure 7 This is a microscopic electron microscope scanning image of the tungsten copper alloy shell prepared in Example 4 before hot isostatic pressing;
[0032] Figure 8 This is a microscopic electron microscope scanning image of the tungsten copper alloy shell prepared in Example 4 after hot isostatic pressing;
[0033] Fig. 9 This is a microscopic electron microscope scanning image of the ultrafine tungsten-copper composite powder prepared in Comparative Example 4;
[0034] Fig.10 This is a microscopic electron microscope scanning image of the ultrafine tungsten-copper composite powder prepared in Comparative Example 5. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and various embodiments and verification examples. It should be understood that the specific embodiments and verification examples described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.
[0036] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this method adopt conventional test methods in the art. The terms described in the present invention are only for describing specific implementation methods and are not intended to limit the content disclosed in the present invention.
[0037] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the invention belongs; other raw materials, reagents, experimental methods and technical means not specifically specified in the present invention refer to the raw materials and reagents commonly used by ordinary technicians in the field, as well as the commonly used experimental methods and technical means.
[0038] Example 1
[0039] In this example, the following steps were performed to prepare Figure 2 Tungsten copper alloy shell with the following structure:
[0040] Step 1: Preparation of ultrafine tungsten-copper composite powder. Prepare a solution of ammonium metatungstate and copper nitrate according to the stoichiometric ratio. After centrifugal spray drying, the solution is subjected to ultrafine tungsten-copper composite powder precursor. The precursor powder is placed in an air atmosphere for calcination. After calcination, it is further reduced in a hydrogen atmosphere to obtain an ultrafine tungsten-copper composite powder. The microscopic morphology is shown in the figure. Figure 1 As shown in the figure, the average particle size of the powder is 0.8μm, and the mass fraction of copper in the tungsten-copper composite powder is about 30%. Three points in the figure are selected for analysis, and the element composition is shown in Table 1:
[0041] Table 1 Figure 1The element composition of any three points
[0042] element Optional point 1 (Wt%) Optional point 2 (Wt%) Optional point 3 (Wt%) Cu 30.09 29.98 30.03 W 69.91 70.02 69.97
[0043] Step 2: Feed preparation. Add the ultrafine tungsten copper composite powder and the paraffin-based binder into an internal mixer for mixing, and then crush to obtain a tungsten copper composite feed. The weight percentage of the paraffin-based binder in the composite feed is 10%, and the paraffin-based binder is composed of paraffin, polyethylene, polypropylene, polyethylene glycol, and stearic acid, with weight percentages of 52%, 28%, 10%, 8%, and 2%.
[0044] Step 3: Injection molding. Add the tungsten copper composite feed into the injection molding machine to form a tungsten copper complex part injection blank, the injection temperature is 130℃, and the mold temperature is 30℃.
[0045] Step 4: Degreasing. The tungsten copper complex parts are degreased by solvent degreasing and thermal degreasing in turn to obtain degreased blanks. Solvent degreasing is to immerse the injection blank in 45°C n-heptane for 24 hours, and thermal degreasing is to degrease the injection blank after solvent degreasing under negative pressure in a nitrogen atmosphere for 20 hours. The thermal degreasing temperature is 700°C and the holding time is 4 hours.
[0046] Step 5: Sintering. The degreased blank is placed on a ceramic support plate and placed in a continuous sintering furnace in a hydrogen-nitrogen mixed gas atmosphere for sintering at a sintering temperature of 1400°C to obtain a sintered blank for a tungsten-copper complex part.
[0047] Step 6: Hot isostatic pressing. After the sintered blank is subjected to hot isostatic pressing, the tungsten copper alloy shell parts are finally obtained. Figure 3 The hot isostatic pressing treatment temperature is 1140±10°C, the pressure is 200MPa, and the atmosphere is argon.
[0048] The density and leakage rate of the prepared tungsten-copper alloy shell parts were tested. The results showed that the density of the tungsten-copper alloy shell was 99.5%, and the leakage rate was 0.9×10 -9 Pa·m 3 / s.
[0049] Example 2
[0050] In this example, the following steps were performed to prepare Figure 4 Tungsten copper alloy shell with the following structure:
[0051] Step 1: Preparation of ultrafine tungsten-copper composite powder. Tungsten trioxide and copper oxide powder are mixed in a mixer according to the stoichiometric ratio. The mixture is calcined in an air atmosphere and reduced in a hydrogen atmosphere to obtain ultrafine tungsten-copper composite powder. The microscopic morphology is shown in the figure. Figure 3As shown in the figure, the average particle size of the powder is 0.6μm, and the mass fraction of copper in the tungsten-copper composite powder is about 20%. Three points in the figure are selected for analysis, and the element composition is shown in Table 2:
[0052] Table 2 Figure 3 The element composition of any three points
[0053] element Optional point 1 (Wt%) Optional point 2 (Wt%) Optional point 3 (Wt%) Cu 20.11 20.04 20.26 W 79.89 79.96 79.74
[0054] Step 2: Feed preparation. Add the ultrafine tungsten copper composite powder and the polyoxymethylene-based binder into an internal mixer for mixing, and crush to obtain a tungsten copper composite feed. The weight percentage of the polyoxymethylene-based binder in the composite feed is 6%, and the polyoxymethylene-based binder is composed of polyoxymethylene, high-density polyethylene, polypropylene, and ethylene-vinyl acetate copolymer, with weight percentages of 89%, 6%, 3%, and 2%.
[0055] Step 3: Injection molding. Add the tungsten copper composite feed into the injection molding machine to form a tungsten copper complex part injection blank, the injection temperature is 160℃, and the mold temperature is 37℃.
[0056] Step 4: Debinding. The tungsten copper complex parts are subjected to catalytic debinding and thermal debinding in turn to obtain debinded blanks. Catalytic debinding is to place the injection blank in nitric acid vapor at a temperature of 135°C and a concentration of 70% for 3 hours. Thermal debinding is to place the injection blank after catalytic debinding in a hydrogen-nitrogen mixed gas at positive pressure for 15 hours. The thermal debinding temperature is 500°C and the holding time is 2 hours.
[0057] Step 5: Sintering. The degreased blank is placed on a ceramic support plate and placed in a batch furnace with ammonia decomposition gas for sintering at a sintering temperature of 1200°C to obtain a sintered blank for tungsten-copper complex parts.
[0058] Step 6: Hot isostatic pressing. After the sintered blank is subjected to hot isostatic pressing, the tungsten copper alloy shell parts are finally obtained. Figure 4 The hot isostatic pressing temperature is 1120±10°C, the pressure is 180MPa, and the atmosphere is argon.
[0059] The density and leakage rate of the prepared tungsten-copper alloy shell parts were tested. The results showed that the density of the tungsten-copper alloy shell was 99.4% and the leakage rate was 0.85×10 -9 Pa·m 3 / s.
[0060] Example 3
[0061] In this example, the following steps were performed to prepare Figure 6 Tungsten copper alloy shell with the following structure:
[0062] Step 1: Preparation of ultrafine tungsten-copper composite powder. Tungsten powder with a particle size of ≤3μm, copper powder with a particle size of ≤3μm and tungsten balls are added to a high-energy ball mill for mechanical alloying. The weight percentage of tungsten powder and copper powder is 9:1. The speed of the high-energy ball mill is 300r / min, and the ball milling time is 24h. Ultrafine tungsten-copper composite powder is obtained. Its microscopic morphology is shown in the figure below. Figure 5 As shown in the figure, the average particle size of the powder is 0.4μm, and the mass fraction of copper in the tungsten-copper composite powder is about 10%. Three points in the figure are selected for analysis, and the element composition is shown in Table 3:
[0063] Table 3 Figure 5 The element composition of any three points
[0064] element Optional point 1 (Wt%) Optional point 2 (Wt%) Optional point 3 (Wt%) Cu 10.03 10.15 10.08 W 89.97 89.85 89.92
[0065] Step 2: Feed preparation. Add the ultrafine tungsten copper composite powder and the paraffin-based binder into an internal mixer for mixing, and crush to obtain a tungsten copper composite feed. The weight percentage of the paraffin-based binder in the composite feed is 3%, and the paraffin-based binder is composed of paraffin, polyethylene, polypropylene, polyethylene glycol, and stearic acid, with weight percentages of 52%, 28%, 10%, 8%, and 2%.
[0066] Step 3: Injection molding. Add the tungsten copper composite feed into the injection molding machine to form a tungsten copper complex part injection blank, the injection temperature is 180℃, and the mold temperature is 45℃.
[0067] Step 4: Degreasing. The tungsten copper complex parts are degreased by solvent degreasing and thermal degreasing in turn to obtain degreased blanks. Solvent degreasing is to immerse the injection blank in dichloromethane at 40°C for 4 hours, and thermal degreasing is to degrease the injection blank after solvent degreasing in a hydrogen atmosphere at positive pressure for 5 hours. The thermal degreasing temperature is 300°C and the holding time is 1 hour.
[0068] Step 5: Sintering. The degreased blank is placed on a ceramic support plate and placed in a continuous sintering furnace in a pure hydrogen atmosphere for sintering at a sintering temperature of 1100°C to obtain a sintered blank for a tungsten-copper complex part.
[0069] Step 6: Hot isostatic pressing. After the sintered blank is subjected to hot isostatic pressing, the tungsten copper alloy shell parts are finally obtained. Figure 6 The hot isostatic pressing temperature is 1090±6°C, the pressure is 100MPa, and the atmosphere is argon.
[0070] The density and leakage rate of the prepared tungsten-copper alloy shell parts were tested. The results showed that the density of the tungsten-copper alloy shell was 99.2% and the leakage rate was 0.95×10 -9 Pa·m 3 / s.
[0071] Example 4
[0072] Steps 1 to 5 of this embodiment are the same as those of embodiment 2. The obtained sintered blank of the tungsten-copper complex part is shown in the following figure: Figure 7 As shown in Figure 2, the density of the material is 97.5%, and there are many closed residual pores in the material (such as Figure 7 The inhomogeneity of the internal structure of the material can be reflected by the change of microhardness. The microhardness HV10 of 5 points was randomly measured (Table 4), and there was a large fluctuation. According to the GJB 360B-2009 standard, the leakage rate of the material was 3×10 -9 Pa·m 3 / s. The density of the sintered blank of tungsten copper complex parts can reach 99.2% by hot isostatic pressing (1100±10℃, 180MPa, 1h), and the residual pores inside the material are almost eliminated ( Figure 8 ), the sintering necks between tungsten particles increased, the microhardness and its uniformity were significantly improved (Table 4), and the leakage rate of the material was 0.86×10 -9 Pa·m 3 / s.
[0073] Table 4 Microhardness of sintered blank of tungsten copper complex parts before and after hot isostatic pressing
[0074]
[0075] Comparative Example 1
[0076] The powder in step 1 of Example 1 was replaced with tungsten powder with a particle size of 1.2 μm and copper powder with a particle size of 1.2 μm, which were added into a mixer and mixed evenly. The weight percentage of tungsten powder and copper powder was 7:3. The mixing time was 24 h. The particle size of the obtained tungsten-copper mixed powder was 1.2 μm. The rest of the processes were the same as in Example 1.
[0077] The obtained tungsten copper alloy shell has a density of 98.5% and a leakage rate of 1.5×10 -9 Pa·m 3 / s.
[0078] Comparative Example 2
[0079] The hot isostatic pressing temperature in step six of Example 1 is changed to 1165±10°C, and the rest of the processes are the same as in Example 1.
[0080] After hot isostatic pressing, it was found that the copper liquid flowed out of the surface of the parts. The density and leakage rate of the tungsten-copper alloy parts were tested. The results showed that the density of the tungsten-copper alloy shell was 98.8% and the leakage rate was 1.3×10 -9 Pa·m 3 / s.
[0081] Comparative Example 3
[0082] The hot isostatic pressing temperature in step six of Example 1 is changed to 1070±10°C, and the remaining processes are the same as in Example 1.
[0083] The density and leakage rate of the tungsten copper alloy parts were tested. The results showed that the density of the tungsten copper alloy shell was 98.1% and the leakage rate was 1.9×10 -9 Pa·m 3 / s.
[0084] Comparative Example 4
[0085] This comparative example is discussed on the basis of Example 3:
[0086] Step 1: Preparation of ultrafine tungsten-copper composite powder. Tungsten powder with a particle size of ≤3μm and copper powder with a particle size of ≤3μm are separately ball-milled in a high-energy ball mill. The speed of the high-energy ball mill is 300r / min and the ball milling time is 24h. The ball-milled tungsten powder and copper powder are added to a V-type mixer at a weight percentage of 9:1 for mixing. The mixing time is 36h and the speed of the V-type mixer is 40r / min to obtain ultrafine tungsten-copper composite powder. Its microscopic morphology is shown in the figure below. Fig. 9 As shown, the average particle size is 0.5μm. The tungsten copper powder is mixed unevenly in many places. The six points with the most uneven mixing are selected for analysis. The element composition is shown in Table 5:
[0087] Table 5 Fig. 9 The element composition of any six points in
[0088]
[0089] The rest of the process is the same as that of Example 3.
[0090] The density and leakage rate of the tungsten copper alloy parts were tested. The results showed that the density of the tungsten copper alloy shell was 98.9% and the leakage rate was 2.6×10 -9 Pa·m 3 / s.
[0091] Comparative Example 5
[0092] This comparative example is discussed on the basis of Example 3:
[0093] Step 1: Preparation of ultrafine tungsten-copper composite powder. Tungsten powder with a particle size of ≤3μm, copper powder with a particle size of ≤3μm and tungsten balls are added to a high-energy ball mill for mechanical alloying. The weight percentage of tungsten powder and copper powder is 9:1. The speed of the high-energy ball mill is 150r / min, and the ball milling time is 24h. Ultrafine tungsten-copper composite powder is obtained. Its microscopic morphology is shown in the figure below. Fig.10As shown, the average particle size is 1.6μm. Select any three points in the figure for analysis, and the elemental composition is shown in Table 6:
[0094] Table 6 Fig.10 The element composition of any three points
[0095] element Optional point 1 (Wt%) Optional point 2 (Wt%) Optional point 3 (Wt%) Cu 10.21 10.02 9.94 W 89.79 89.98 90.06
[0096] The rest of the process is the same as that of Example 3.
[0097] The density and leakage rate of the tungsten copper alloy parts were tested. The results showed that the density of the tungsten copper alloy shell was 98.0% and the leakage rate was 2.2×10 -9 Pa·m 3 / s.
[0098] The above-mentioned embodiments and verification examples only express the specific implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, which all belong to the scope of protection of the present application.
Claims
1. A method for preparing complex-shaped parts of tungsten-copper alloy for high-airtightness packaging, characterized in that: The steps include: (1) preparing ultrafine tungsten-copper composite powder by any of the following methods: wet mixing of tungsten precursor and copper precursor, followed by drying, calcining and reducing; or mixing of tungsten oxide and copper oxide, followed by calcining and reducing; Or by mixing tungsten powder and copper powder and then obtaining it by mechanical alloying method; The average particle size of the obtained ultrafine tungsten-copper composite powder is 0.4-0.9 μm, the mass fraction of copper in the tungsten-copper composite powder is 5-40%, and the tungsten-copper powder is evenly mixed; (2) The ultrafine tungsten-copper composite powder and the organic binder are mixed and granulated to prepare a feed for injection, and then the feed is injected into a mold. After demolding, the injection blank of the part is obtained, and then degreasing, high-temperature sintering and hot isostatic pressing are performed to obtain a tungsten-copper alloy complex-shaped part for high-airtightness packaging, wherein the high-temperature sintering temperature is 1100-1600° C., and the sintering atmosphere is one of pure hydrogen, hydrogen-nitrogen mixed gas or ammonia decomposition gas; the hot isostatic pressing temperature is 1084-1150° C., the pressure is 100-200 MPa, and the atmosphere is argon; wherein the organic binder is a paraffin-based binder or a polyoxymethylene-based binder, and the weight proportion of the organic binder to the total material is 3-10%.
2. The preparation method according to claim 1, characterized in that The paraffin-based adhesive is composed of the following components in weight percentage: 52% paraffin, 28% polyethylene, 10% polypropylene, 8% polyethylene glycol, and 2% stearic acid.
3. The preparation method according to claim 2, characterized in that: The degreasing operation corresponding to the paraffin-based binder includes solvent degreasing and thermal degreasing performed in sequence.
4. The preparation method according to claim 1, characterized in that: The polyoxymethylene-based adhesive is composed of the following components in weight percentage: 89% polyoxymethylene, 6% high-density polyethylene, 3% polypropylene, and 2% ethylene-vinyl acetate copolymer.
5. The preparation method according to claim 4, characterized in that: The degreasing operation corresponding to the polyoxymethylene-based binder includes catalytic degreasing and thermal degreasing performed in sequence.
Citation Information
Patent Citations
Technique for preparing tungsten copper heat-sink and electric packaging material
CN101450381A
Preparation method for silver-loaded nano particle temperature stimuli responsiveness hybrid nanofiber membrane
CN104928851A
Method for preparing double-component tungsten copper alloy through co-injection
CN110172598A
Preparation method of tungsten-copper heat sink component for optical module
CN114535589A
Preparation method of heat sink material injection molding slurry
CN115464144A